Ponatinib Drives Cardiotoxicity by S100A8/A9-NLRP3-IL-1β Mediated Inflammation. Issue 3 (10th January 2023) - Tousif, Sultan; Singh, Anand P.; Umbarkar, Prachi; Galindo, Cristi; Wheeler, Nicholas; Toro Cora, Angelica; Zhang, Qinkun; Prabhu, Sumanth D.; Lal, Hind
Abstract : Background: The tyrosine kinase inhibitor ponatinib is the only treatment option for chronic myelogenous leukemia patients with T315I (gatekeeper) mutation. Pharmacovigilance analysis of Food and Drug Administration and World Health Organization datasets has revealed that ponatinib is the most cardiotoxic agent among all Food and Drug Administration–approved tyrosine kinase inhibitors in a real-world scenario. However, the mechanism of ponatinib-induced cardiotoxicity is unknown. Methods: The lack of well-optimized mouse models has hampered the in vivo cardio-oncology studies. Here, we show that cardiovascular comorbidity mouse models evidence a robust cardiac pathological phenotype upon ponatinib treatment. A combination of multiple in vitro and in vivo models was employed to delineate the underlying molecular mechanisms. Results: An unbiased RNA sequencing analysis identified the enrichment of dysregulated inflammatory genes, including a multifold upregulation of alarmins S100A8/A9, as a top hit in ponatinib-treated hearts. Mechanistically, we demonstrate that ponatinib activates the S100A8/A9-TLR4 (Toll-like receptor 4)-NLRP3 (NLR family pyrin domain–containing 3)-IL (interleukin)-1β signaling pathway in cardiac and systemic myeloid cells, in vitro and in vivo, thereby leading to excessive myocardial and systemic inflammation. Excessive inflammation was central to the cardiac pathology because interventions with broad-spectrum immunosuppressive glucocorticoid dexamethasone or specific inhibitors of NLRP3 (CY-09) or S100A9 (paquinimod) nearly abolished the ponatinib-induced cardiac dysfunction. Conclusions: Taken together, these findings uncover a novel mechanism of ponatinib-induced cardiac inflammation leading to cardiac dysfunction. From a translational perspective, our results provide critical preclinical data and rationale for a clinical investigation into immunosuppressive interventions for managing ponatinib-induced cardiotoxicity.